Creating caring environments: An exploration of football managers and coaching - Agnew, D.; Pill, S. (Sports Coaching Review, 2023)
This study explored the experiences of Football Managers and coaching staff in providing care for footballers who are deselected from an elite Australian football (AFL) team and chose to continue playing at the semi-professional state-league level. Deselected athletes are particularly vulnerable to difficult transitions because they have little control over the timing of their retirement. A narrative inquiry was utilised to explore four participants` experiences in providing care for Australian footballers who have been deselected from the elite competition and who have returned to state-based leagues. Three themes were identified in the data; the need for care; more than football and under-resourcing. In line with Nodding`s notion that the "carer must act" it was established that football clubs have a duty to care for footballers and encourage the holistic development of the whole person. Resourcing is a major barrier in the ability to create caring environments in state-based football clubs.